Continuous Production of Nanotubes and Carbon Clusters by Use of the Revolver-Injection-Type Arc Jet Producer - Mieno, Tetsu; Matsumoto, Naoki; Tomie, Takahashi; Inoue, H. (Makara Journal of Technology, 2014)
Efficient and continuous production of fullerenes, single-walled carbon nanotubes (SWNTs), and carbon nano-particles has been developed by the JxB arc jet method, where the Lorentz force of magnetic field jets out gaseous carbon particles to the JxB direction. In order to realize continuous mass production of these carbon clusters, the revolverinjection- type arc jet producer (RIT-AJP) has been developed. Production of fullerenes, endohedral metallo-fullerenes, SWNTs, metal-encapsulated carbon nano particles has been examined.